2002
DOI: 10.1161/01.atv.0000026614.72957.e7
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Genetic Evidence That Tranilast Reduces Smooth Muscle Cell Hyperplasia via a p21 WAF1 -Dependent Pathway

Abstract: Objective-N-(3Ј4Ј-dimethoxycinnamoyl)-anthranilic acid (tranilast) is a drug that has been shown to reduce the incidence of restenosis after angioplasty in middle-scale clinical trials. Despite clinical interest in this drug, the pharmacological actions of tranilast remain relatively unexplored at a molecular level. Methods and Results-We evaluated the effects of tranilast on vascular smooth muscle cell (VSMC) proliferation in wild-type mice and in mice lacking a cyclin-dependent kinase inhibitor, p21 WAF1 (p2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…To date, supporting evidence has included the observation that overexpression of recombinant p21 Cip1 decreases VSMC proliferation and attenuates the progression of vascular proliferative diseases (21,23,24,26) and that, conversely, reduced p21 Cip1 expression leads to increased neointimal formation following arterial injury (28). This has led to the evaluation of novel treatment strategies for these diseases that are at least partially mediated through p21 Cip1 upregulation (25,56,57). Our results further extend this work and serve to reinforce the important role of p21 Cip1 in modulating vascular wound repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, supporting evidence has included the observation that overexpression of recombinant p21 Cip1 decreases VSMC proliferation and attenuates the progression of vascular proliferative diseases (21,23,24,26) and that, conversely, reduced p21 Cip1 expression leads to increased neointimal formation following arterial injury (28). This has led to the evaluation of novel treatment strategies for these diseases that are at least partially mediated through p21 Cip1 upregulation (25,56,57). Our results further extend this work and serve to reinforce the important role of p21 Cip1 in modulating vascular wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…p21 Cip1 transcription is activated by p53, and p21 Cip1 is part of a negative feedback mechanism that controls p53 activity during apoptosis (20). p21 Cip1 has been shown to be an important mediator of inflammation, VSMC proliferation (21,22), and vascular proliferative disease (23)(24)(25)(26)(27). Of particular relevance, p21 knockout mice have been shown to exhibit enhanced neointimal formation following arterial injury (28).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of p21 WAF1 in VSMCs has been shown to be crucial in the termination of vascular lesion formation 33) . Moreover, Sata et al demonstrated that tranilast failed to inhibit VSMC proliferation when endogenous p21 was genetically ablated 17) . In the same way, we showed that TSA failed to inhibit proliferation in VSMCs from p21 WAF1 knock-out mice, although there may be different mechanism(s) in the inhibitory effect between tranilast and TSA.…”
Section: Discussionmentioning
confidence: 99%
“…The second group is comprised of p21 WAF1 /p27 KIP1 family members that block cell-cycle progression by inhibiting cyclin D-, E-, and A-associated Cdk complexes 15) . Previously we and colleagues have demonstrated that tranilast, N -(3',4'-dimethoxycinnamoyl) anthranilic acid, inhibits SMC proliferation by the inhibition of Rb phosphorylation and CDK2/CDK4 activities by the increased expression of p21 WAF1 in vitro and in vivo after vascular injury 16,17) . In eukaryotic cells, chromatin must be remodeled in order to render DNA accessible to the actions of transcription factors 18) .…”
Section: Introductionmentioning
confidence: 98%
“…Male mice were anesthetized by inhalational isoflurane (maintenance rate of 1.5%), and endoluminal injury to the common femoral artery was performed with a method similar to that of Sata et al 18 A 0.12-mm wire was inserted distal to the muscular branch artery and passed 6 times back and forth along the common femoral artery. The arteriotomy site was subsequently ligated.…”
Section: Wire Injurymentioning
confidence: 99%